“You Can Enter but You Cannot Leave…”: U.S. Securities Markets and Foreign Firms - MAROSI, ANDRÁS; MASSOUD, NADIA (Journal of Finance, 2008)
ABSTRACT Although a number of prior papers have argued the benefits to foreign firms of cross‐listing their shares in the U.S., the number of foreign firms exiting U.S. capital markets has been increasing. This has occurred despite the difficulties foreign firms face in deregistering from the Securities and Exchange Commission (SEC). This paper examines the reasons underlying this trend. One of our main findings is that the passage of the Sarbanes‐Oxley Act has reduced the net benefits of a U.S. listing and registration, particularly for smaller foreign firms with lower trading volume and stronger insider control.